Effects of Food Advertising on Youth’s Eating Behavior: A Systematic Review of Longitudinal Studies - Ángela-Justine González Geuder; Natalia Martín-María (Clínica y Salud. Investigación Empírica en Psicología, 2025)

(untitled)
Background:Previous cross-sectional studies have found a positive relationship between commercial audiovisual media viewing and youth overweight/obesity, suggesting that advertising of low-nutritional-value products (LNVP) influences unhealthy food consumption patterns. The objective of this study was to analyze the long-term influence of LNVP advertising on children’s and adolescents’ consumption habits.Method:A systematic literature review following PRISMA guidelines examined the long-term effects of LNVP advertising on youth’s diet-related outcomes. A search in PubMed and PsycINFO (June 2024) included studies from the last 12 years exploring the relationship between digital food advertising and subsequent consumption behaviors. Two authors independently screened and assessed studies using an adapted Newcastle-Ottawa Scale. Results: Findings were inconclusive, with six of twelve studies reporting a positive relationship, while the other six found no association. Conclusions: LNVP advertising does not enhance youth’s food choices or nutritional knowledge. Its impact on diet appears limited and may depend on other factors, such as parental nutritional knowledge.